A Literature Review: Analyzing the Rawa Pening Folktale to Foster Character Education in Elementary School - Nurul Farhin; Galih Cahya Pratama (Universitas Negeri Semarang, 2025)
This study aims to analyze the character values contained in the Rawa Pening folklore and their relevance to character education in elementary schools. This research is a type of literature study, which is used to explore the topic related to the character values embedded in the Rawa Pening folklore and their implementation for elementary school students.Literature was collected from Google Scholar using the keywords “character values” and “Rawa Pening folklore.” The inclusion criteria for source selection included publications from 2021 to 2025. A total of 7 relevant and representative articles were selected for further analysis. The data were analyzed through a process of classification and categorization, thematic analysis, and synthesis and interpretation. Based on the results of the literature review, it was found that the Rawa Pening folklore holds strong potential for instilling character values in elementary school students, such as responsibility, empathy, and humility, which can be internalized through classroom learning activities.